Correlation Between the Clinical Parameters and Tissue Phenotype in Patients Affected by Deep-Infiltrating Endometriosis. (September 2016) - Vinci, Giovanna; Arkwright, Sylviane; Audebourg, Anne; Radenen, Brigitte; Chapron, Charles; Borghese, Bruno; Dousset, Bertrand; Mehats, Celine; Vaiman, Daniel; Vacher-Lavenu, Marie-Cécile; Gogusev, Jean
The current study aimed to identify and validate an applicable immunohistochemistry panel including Ki-67, c-MYC, estrogen receptor-α (ER-α), and progesterone receptor isoforms A/B (PR-A/B) in correlation with clinicopathological parameters in patients affected by deep infiltrating endometriosis. Tissue microarrays were prepared from a cohort of 113 patients. Phenotypic profile of the panel molecules was evaluated in glands and stroma in parallel with microvessels and stroma density measurements. Principal component analysis was performed on 8 immunohistochemical variables, 2 histological variables, and 8 subgroups of clinical parameters. The immunohistochemical profiling showed consistent Ki-67 immunostaining in 17.9% of the samples and c-MYC in 83.1%, while intense ER-α immunoreactivity was detected in 84% of the samples and PR-A/B isoforms in 24.1% of them. The combination of clinical parameters and tissue phenotype allowed a stratification of endometriosis-affected patients. Such novel phenotypical and clinical correlation could be helpful in the future studies for a better stratification of the disease aiming at a personalized patient care.